Eksplorasi Tantangan dan Strategi Koping pada Caregiver Anak Berkebutuhan Khusus - Rita Untari; Maharso Adhi Nugroho; Nadia Aulia (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Raising a child with special needs can be difficult and stressful, making it important for parents to have effective coping strategies to manage the stress they experience. Coping can be defined as the cognitive and behavioral efforts made to control, tolerate, or reduce the demands, external and internal conflicts created by stressful situations. Objectives: The aim of this study is to determine the psychological impact and coping strategies of mothers raising children with special needs. Methods: This study used a qualitative method with a phenomenological approach. Data collection was conducted through semi- structured interview (in depth interview) using thematic data analysis. Respondents in this study were seven mothers who care special needs children for a min 1 year and a max 5 years. Results: The results s of the study revealed four main themes: (1) Challenges of Raising Children with Special Needs, with 4 sub-themes: emotional responses, self-acceptance, varied behaviors of children with special needs, and environmental barriers; (2) Impacts on Mothers with Children with Special Needs, with 2 sub-themes: unstable emotions and decreased productivity; (3) Coping Strategies, with 3 sub-themes: religiosity aspects, social support, and me- time; (4) Psychological Resilience, with 2 sub-themes: self-awareness and positive outlook. Conclusion: The challenges for mothers in caring children with special needs are feeling emotional responses, including sadness, self-acceptance such as denial of their child's condition, varying child behavior, and an unsupportive family environment. The impact on mothers with children with special needs is that mothers find it difficult to control their emotions and their productivity decreases. Coping strategies carried out by mothers with children with special needs include religious aspects, social support from the family, and me time. Resilience is needed to overcome the stress of parenting experienced by mothers, such as self- awareness and positive outlook. Keywords: Mothers Caring For Children With Special Needs, Psychological Impact, Coping Strategy.